Laryngeal evidence for the first and second passaggio in professionally trained sopranos. - Matthias Echternach; Fabian Burk; Marie Köberlein; Andreas Selamtzis; Michael Döllinger; Michael Burdumy; Bernhard Richter; Christian Thomas Herbst (PLoS ONE, 2017)
Due to a lack of empirical data, the current understanding of the laryngeal mechanics in the passaggio regions (i.e., the fundamental frequency ranges where vocal registration events usually occur) of the female singing voice is still limited.In this study the first and second passaggio regions of 10 professionally trained female classical soprano singers were analyzed. The sopranos performed pitch glides from A3 (ƒo = 220 Hz) to A4 (ƒo = 440 Hz) and from A4 (ƒo = 440 Hz) to A5 (ƒo = 880 Hz) on the vowel [iː]. Vocal fold vibration was assessed with trans-nasal high speed videoendoscopy at 20,000 fps, complemented by simultaneous electroglottographic (EGG) and acoustic recordings. Register breaks were perceptually rated by 12 voice experts. Voice stability was documented with the EGG-based sample entropy. Glottal opening and closing patterns during the passaggi were analyzed, supplemented with open quotient data extracted from the glottal area waveform.In both the first and the second passaggio, variations of vocal fold vibration patterns were found. Four distinct patterns emerged: smooth transitions with either increasing or decreasing durations of glottal closure, abrupt register transitions, and intermediate loss of vocal fold contact. Audible register transitions (in both the first and second passaggi) generally coincided with higher sample entropy values and higher open quotient variance through the respective passaggi.Noteworthy vocal fold oscillatory registration events occur in both the first and the second passaggio even in professional sopranos. The respective transitions are hypothesized to be caused by either (a) a change of laryngeal biomechanical properties; or by (b) vocal tract resonance effects, constituting level 2 source-filter interactions.